2021
DOI: 10.24198/pjd.vol33no1.23907
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the retentive ability on incisal bite force between aloe vera and poly(methyl-vinyl-ether) adhesive materials in complete acrylic denture measured by modified pressure transducer

Abstract: Introduction: Patients with acrylic complete denture, usually have a confidence issue in using their complete dentures to chew and speak, because of concern about detached of the denture from its place and pain on the alveolar ridge. Application denture adhesive material ordinarily can solve the problem. Mostly, denture adhesives in the market are made from synthetic material poly(methyl-vinyl-ether) but nowadays aloe vera extract is believed to be a substitute to synthetic denture adhesive material. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The findings of this study are supported by several previous studies that demonstrated Uncaria Gambir's ability to fight a variety of bacteria, including: Julinda et al 2021 reported that the combination of various Uncaria gambier solvents has been shown to inhibit and kill E. faecalis. The combination of Ethyl Acetate-water fraction is the best combination against E. faecalis (Julinda et al, 2021). Another study found the gambier extract exerted higher antibacterial activity against gram-negative bacteria E. coli and Salmonella sp.…”
Section: Resultsmentioning
confidence: 97%
“…The findings of this study are supported by several previous studies that demonstrated Uncaria Gambir's ability to fight a variety of bacteria, including: Julinda et al 2021 reported that the combination of various Uncaria gambier solvents has been shown to inhibit and kill E. faecalis. The combination of Ethyl Acetate-water fraction is the best combination against E. faecalis (Julinda et al, 2021). Another study found the gambier extract exerted higher antibacterial activity against gram-negative bacteria E. coli and Salmonella sp.…”
Section: Resultsmentioning
confidence: 97%